2010
DOI: 10.1111/j.1447-0349.2010.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

From numbers to understanding: The impact of demographic factors on seclusion rates

Abstract: The reduction and, where possible, elimination of seclusion has been recognized as a national safety priority for mental health services in Australia, with significant attention devoted to strategies to achieve this goal. The aim of this study was to compare specific demographic characteristics between consumers who have been secluded to those who have not. Patient data (n = 3244) collected by 11 mental health services across Australia for six months over a 12 month period were analysed using demographic stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…A study by Fiorillo et al (2012) in a large sample of inpatients (n = 3093) among 11 European countries revealed that severe psychotic symptoms combined with poor social functioning was associated with higher levels of coercion. One of the options to reduce coercion, and more specifically, high seclusion rates, might be to frequently monitor changes in the mental state and behaviour of admitted patients (Abderhalden et al 2008;Clarke et al 2010;Happell & Koehn 2010;van de Sande et al 2011;Slye et al 2009). There is evidence that admitted acute psychiatric patients often present symptom and behaviour patterns that can fluctuate within hours (Linacker & Bush Iversen 1995;Steinert et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Fiorillo et al (2012) in a large sample of inpatients (n = 3093) among 11 European countries revealed that severe psychotic symptoms combined with poor social functioning was associated with higher levels of coercion. One of the options to reduce coercion, and more specifically, high seclusion rates, might be to frequently monitor changes in the mental state and behaviour of admitted patients (Abderhalden et al 2008;Clarke et al 2010;Happell & Koehn 2010;van de Sande et al 2011;Slye et al 2009). There is evidence that admitted acute psychiatric patients often present symptom and behaviour patterns that can fluctuate within hours (Linacker & Bush Iversen 1995;Steinert et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Patient restrictions, e.g., seclusion/restraint, are widely used in psychiatric hospitals to control challenging behavior in patients experiencing psychosis (Whittington, Bowers, Nolan, Simpson, & Lindsay, 2009). The acute, and diagnostically the most disturbed, patients are at the highest risk of being secluded and restrained (Happell & Koehn, 2010; Keski‐Valkama et al., 2009). Violent behavior or threatening violence is a commonly accepted indication for the use of seclusion/restraint (Whittington et al., 2009).…”
mentioning
confidence: 99%
“…To gain an indication of the health and social functioning of community mental health consumers, several researchers have used the Health of the Nation Outcome Scales ( HoNOS; Wing et al, 1998 ) in their studies (e.g., Happell & Koehn, 2010;Kortrijk, Mulder, Roosenschoon, & Wiersma, 2010;Meagher, O'Brien, Pullela, Oshun, & Brosnan, 2009;Monzani, Erlicher, Lora, Lovaglio, & Vittadini, 2008;Prowse & Coombs, 2009;Rees, Richards, & Shapiro, 2004;Segal, Daffern, Thomas, & Ferguson, 2010).…”
Section: Health and Social Functioningmentioning
confidence: 99%